AMPLIFICATION OF XUV HARMONIC RADIATION IN A GALLIUM AMPLIFIER - Ditmire, T; Hutchinson, M; Key, M; Lewis, C; Macphee, A; Mercer, I; Neely, D; Perry, M; Smith, R; Wark, J; Zepf, M (1995)
We report the observation of amplification of an xuv harmonic pulse in an xuv laser. The 21st harmonic of a frequency-doubled 1.3-psec neodymium chirped-pulse-amplification laser pulse was injected into the gain region of an 18-mm-long Ga XXII x-ray amplifier. A gain of approximately 3 was recorded for the 21st harmonic, relative to the unamplified 19th and 23rd harmonics when the harmonic wavelength was tuned to overlap the 25.11-nm J=2-1 laser transition. © 1995 The American Physical Society.